Evaluation of Anti-inflammatory, Antinociceptive, and Antipyretic Activities of Prunus persica var. nucipersica (Nectarine) Kernel - Elshamy, Abdelsamed Ibrahim; Abdallah, Heba Mohammed Ibrahim; El Gendy, Abd El-Nasser Gaber; El-Kashak, Walla; Muscatello, Beatrice; De Leo, Marinella; Pistelli, Luisa (Planta Medica, 2019)
Nectarine (Prunus persica var. nucipersica) is a worldwide appreciated edible subspecies, with a high nutritional value and benefits on human health due to its phenolic content. Despite the large consumption of the fruit, the potential use of its kernel is poorly studied. Herein, the potential pharmacological activities and the phenolic constituents of an alcoholic extract of kernel nectarine fruits were investigated. Administering nectarine kernel extract (50 and 100 mg/kg, respectively) in rats reduced paw edema after carrageenan injection by 11 and 47% in 1 h, 24 and 33% in 2 h, and 23 and 32% in 4 h, when compared to the controls. At the higher dose (100 mg/kg), nectarine kernel extract increased the reaction time in the hot-plate model and produced a significant decrease in the rectal temperature of the pyretic rats, while both doses produced 52 and 59% of writhing inhibition compared to the control group. Total polyphenolic (55.91 ± 5.78 mg/g) and flavonoid (29.89 ± 0.55 mg/g) content indicated that the extract is a promising source of these constituents. HPLC-ESI-MS/MS analysis demonstrated the presence of flavonoids, such as naringenin and apigenin glycosides. The cyanogenic glycosides amigdalin and prunasin were also detected. These results highlight the anti-inflammatory, analgesic, and antipyretic activities of nectarine kernel alcoholic extract, together with significant phenolic content, promoting its exploitation as a source of bioactive molecules.
Keywords: Prunus persica var. nucipersica; Rosaceae; nectarine kernel; anti-inflammatory; analgesic; antipyretic; LC-PDA-ESI-MS/MS; flavonoids